Control of Listeria monocytogenes and Escherichia coli O157:H7 in enoki mushrooms (Flammulina velutipes) by combined treatments with organic acids, nisin, and ultrasound. (November 2021) - Yoon, Jae-Hyun; Jeong, Do-Young; Lee, Su-Bin; Kim, Se-Ri
Abstract: This study was undertaken to evaluate the combined effect of organic acids, nisin, and ultrasound (US) on the reduction of Listeria monocytogenes and Escherichia coli O157:H7 in enoki mushrooms stored at 5 °C. Each bacterium was treated with 1–3% organic acids, 0.1% nisin, and 40 kHz US in enoki mushrooms individually or in combination at 25 °C for ≤30 min. Lactic acid (LA) was superior to malic acid, acetic acid, and nisin, decreasing L . monocytogenes and E. coli O157:H7 in enoki mushrooms by more than 3.00 log CFU/g at 25 °C for 30 min. US alone failed to inactivate L . monocytogenes and E . coli O157:H7 in enoki mushrooms. Particularly, L . monocytogenes and E . coli O157:H7 diminished to below the detection limits (<1.55 log CFU/g) in enoki mushrooms after dipping in 3% LA and 0.1% nisin incorporated with 40 kHz US at 25 °C for 30 min and remained constant incapable of growing in samples stored at 5 °C for 120 h. A transmission electron microscopy analysis presented collapse of peripheral cytoplasm layers with formation of local pores and breakage of cell wall structures in L . monocytogenes exposed to combined treatments with 3% LA, 0.1% nisin, and 40 kHz US. A combination of LA, nisin, and US exerted strong synergistic effects for controlling the mushroom carriage of L. monocytogenes and E . coli O157:H7.